Lodo de esgoto e adubação mineral na recuperação de atributos químicos de solo degradado - Bonini, Carolina S. B. [UNESP]; Alves, Marlene C. [UNESP]; Montanari, Rafael [UNESP] (Univ Federal Campina Grande, 2015)
The objective of this work was to study the influence of sewage sludge and of mineral fertilization on recovery of chemical properties of a degraded Oxisol, cultivated for four years with eucalyptus and pasture, in Selviria, MS, Brazil. The treatments were: T: control (soil under eucalyptus and pasture without the use of sewage sludge and mineral fertilizers): AM: soil under eucalyptus and pasture with mineral fertilization; D30: soil under eucalyptus and pasture with 30 Mg ha(-1) of sewage sludge; D60: soil under eucalyptus and pasture with 60 Mg ha(-1) of sewage sludge; and two control areas: VN: Native 'Cerrado'vegetation and SE: Bare soil (no tillage and without planting). Soil samples were collected in four soil layers (0 to 0.05, 0.05-0.10, 0.10-0.20 and 0.20-0.40 m) and evaluated for the chemical attributes: phosphorus, organic matter, pH and base saturation. It is concluded that there were positive effects of sewage sludge on the recovery of chemical properties of soil.

Objetivou-se, neste trabalho, estudar a influência do lodo de esgoto e adubação mineral na recuperação de atributos químicos de um Latossolo Vermelho degradado, cultivado há quatro anos, com eucalipto e braquiária. O delineamento experimental utilizado foi inteiramente casualizado com seis tratamentos e quatro repetições. Os tratamentos foram: T: testemunha (solo cultivado com eucalipto e braquiária sem uso do lodo de esgoto e adubação mineral); AM: solo cultivado com eucalipto e braquiária com adubação mineral; D30: solo cultivado com eucalipto e braquiária com 30 Mg ha-1 de lodo de esgoto; D60: solo cultivado com eucalipto e braquiária com 60 Mg ha-1 de lodo de esgoto e duas áreas foram utilizadas como testemunhas: VN: vegetação nativa do cerrado e SE: solo exposto. Foram avaliados os atributos químicos do solo: fósforo, potássio, cálcio, magnésio, matéria orgânica; acidez potencial, pH, soma de bases, capacidade de troca catiônica e saturação por bases, em quatro camadas do solo: 0-0,05; 0,05-0,10; 0,10-0,20 e 0,20-0,40 m. Os resultados indicaram que ocorreram efeitos positivos do lodo de esgoto quanto à recuperação dos atributos químicos do solo.
Sewage sludge and mineral fertilization on recovery of chemical properties of a degraded soil
Keywords: Degraded soil; Eucalyptus citriodora; Brachiaria decumbens